Recalcitrant Interactions : Semiotic Reflections on Fieldwork among Mountain Ascetics - Padoan, Tatsuma (Revista Acta Semiotica, 2021)
This article explores issues related to ethnographic research, such as “otherness” as a form of relation, the researcher’s position, and the difference between anthropological and native knowledge, leading to the production of ethnographic data that can undermine previously established models. In order to approach these issues, I will refer to the notion of “recalcitrant subjects”, coined by I. Stengers, and based on the idea that we should turn our attention to objects of analysis that are capable of raising new questions, forcing the researchers to reorganise their instruments and theoretical perspectives. Using the interaction regimes formulated by E. Landowski, I will analyse from a semiotic perspective my own field research, conducted within the mountain ascetic group Tsukasakō in Katsuragi, central Japan. The article shows how, far from being based on forms of communality and undifferentiated reciprocity, ethnography and sociality always involve heterogeneous actors and can only emerge from interactions that are inherently recalcitrant.